An analysis of unsuccessful offensive sequences in two top level football teams - Barbosa, A.; Sarmento, H.; Planas Anzano, A.; Campanico, J. (World Congress of Performance Analysis of Sport IX, 2012)
The main purpose of this study was to investigate the existence of regular behavior patterns regarding the offensive sequences that ended unsuccessfully. For that, we analyzed two top level teams (Real Madrid, 2010/2011, and International Milan, 2009/2010) that share the same coach and the same technical staff. To collect data, we used the instrument developed and validated by Sarmento et al. (2010). This instrument consists in a specific notation analysis to study the offensive process and its variables. Several offensive sequences were coded through the observation of 24 games of Inter Milan and Real Madrid (12 per each team). In order to verify pattern occurrence, we used the software THÈME 5.0, which is a professional system for detecting and analyzing hidden behavioral patterns, by performing intensive structural analysis of behavioral data. It detects complex repeated patterns that would otherwise remain hidden. The reliability of the data was calculated by the intra and inter observer agreement, and values above 0.95 were achieved for all the variables. For pattern detection, we only considered the ones that were repeated, at least, 9 times, and the significance level was set at 0.005. We detected 11659 T-patterns, of which 4 are complete t-patterns, regarding seven length distribution, from ball recovery until the end of the offensive process (O.P.). In all recorded patterns the last actions occurred in the central zone of the offensive third (zone 11), in an interaction context of relative numerical inferiority. We observed a greater activation of central and right corridor in the offensive midfield. The analysis of the T-patterns complements previous research. We analyzed the three actions preceding the end of the offensive process, and verified the occurrence of at least two actions in the central corridor, in the offensive midfield. The ball only enters in the offensive sector when the offensive process ends. The patterns reflect the use close field zones using a short game. The tree actions before losing the ball possession occurred more often in the right and central corridors. These facts increase the time for the opponent to develop a correct defensive organization placing more players involved in the process. None of the observed the patterns had the actions dribble or ball conduction. In all patterns analyzed the loss of possession occurs in the central zone of the offensive third (zone 11), and in a context of numerical inferiority. The failure occurred above seems to reflect the importance, of using quick pace making use of long pass, play with fewer touches on the ball, ball conduction, dribble and the increase number of players involved in the O.P.. None of the referred to actions occur prior to the end of the offending process.